EBAO solution : a case study of NTUC Income Insurance Cooperative Limited. - Hu, Jasmine Jiawei. (2008)
This report uses NTUC Income as a case study to discover the problems leading to an system migration, the benefits of migration, the migration process, as well as collaboration with offshore vendor.